Perceiving a calling – the effects of demands-abilities misfit, job insecurity and growth mindset - Woon, Shiyi Gail (2020)
The current study investigated the indirect effect model of perceiving a calling on turnover intention for working adults by examining propositions from the Work as Calling model by Duffy et.al (2018). We used demands-abilities misfit and job insecurity as mediators in our model. In addition, we looked at growth mindset as a moderator between demands-abilities misfit and job insecurity. Five hypotheses were created and our results showed that our indirect model was supported. Interestingly, growth mindset as a moderator was not supported. Combining survey with past research, we provide empirical support for our hypotheses.